Estudio de viabilidad técnica y económica de modernización del alumbrado público ubicado sobre la carrera 7 entre calles 13 y 22 del municipio de Soacha (2022)
This project arises from the need for a technical and economic feasibility study of modernization in public lighting located on Carrera 7 between streets 13 and 22 in Soacha, the above was obtained by collecting information about the existing infrastructure, and subsequent to this, measuring the lighting levels in the project area through the lux meter supplied by the company Sociluz; using the information obtained through the measurement, we proceed with the elaboration of the lighting design, when compared with current technology, it demonstrates the technical and economic viability of modernization.